Analisys of Trends And Patterns of Hololive ID Vtubers on Content Variation for Monetization Optimization Using Multiple Linear Regression Algorithm - Aulia, Ananda; Iqbal, Muhammad; Khairul, K (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
YouTube, as a new form of mass media in the advancement of increasingly sophisticated technology, caters to a diverse audience seeking daily information. Many YouTube users leverage this platform as a medium for creativity and income generation, such as through video blogs, educational videos, gaming videos, and various other content. Not all YouTubers can express themselves directly or through livestreaming; some use virtual 2D or 3D characters created with computer software, utilizing technologies such as Face Tracking and Hand Tracking. Hololive Production is a Japanese VTuber agency owned by the Japanese technology company Cover Corporation. Hololive Indonesia (Hololive ID) was established to produce Indonesian-language VTuber content and has garnered significant attention from fans in Indonesia and worldwide. VTuber content primarily revolves around video game topics, indicating a strong interest among VTuber fans in gaming-related content. Moreover, the analysis results show that multiplayer games enabling interaction among VTubers or even with viewers are highly favored, further supporting the popularity of gaming topics among VTuber enthusiasts. The Multiple Linear Regression algorithm has been widely used for sales predictions related to buyer patterns and trends. The performance measurement is influenced by the amount of data and the number of attributes.